The Clinical Findings and Prophylactic Treatment in Children with Factor X Deficiency. (1st November 2013) - Karabel, Müsemma; Söker, Murat; Yıldırım, Aysen Türedi; Oymak, Yeşim; Kelekçi, Selvi; Karabel, Duran
<x xml:space="preserve">Abstract</x> Factor X (FX) is the component of both extrinsic and intrinsic coagulation cascade and is the first enzyme of the common pathway which results in thrombus. Congenital FX deficiency (FXD) is an extremely rare coagulation defect. In this study, we aimed to investigate the clinical and laboratory data of the patients diagnosed with FXD. The files of the 15 patients (7 female, 8 male) diagnosed and followed up for FXD within the last 4 years were evaluated retrospectively. The mean age of the patients was 29 months (min-max:1-144 months). The most presenting complaints were easy bruisability (n = 8; 53%) and epistaxis (n = 8; 53%). FX levels were <1% in six patients, 1–5% in four patients, and >5% in five patients. Heparin added-Protrombin Complex was used for prophlaxy (n = 11; 73%). Any treatment-related complication was not observed. Heparin-added PCC can be used safely for effective prophlaxy. We suggest that family history is important when considering prophlaxy and in patients with life-threatening bleeding or with FXD sibling the prophlaxy should be introduced in the early course.